Corrigendum - Zoellner Y; Balp MM; Gili Marco A (Dove Medical Press, 2011)
York Zoellner1, Maria-Magdalena Balp2, Andrea Gili Marco21Hamburg University of Applied Sciences, Hamburg, Germany; 2Novartis Pharma AG, Basel, SwitzerlandThe role of galenic innovation in improving treatment compliance and persistence: three case studies. Clinicoecon Outcomes Res. 2011;3:109-116. In the results section of the abstract, "...+15% in Germany for desferrioxamine vs deferasirox." should read "...+15% in Germany for deferasirox vs desferrioxamine." In the ‘Compliance' section, "...and +15% in Germany for desferrioxamine vs deferasirox." should read "...and +15% in Germany for deferasirox vs desferrioxamine."Original Article